Relevansi Pemikiran John C. Maxwell Untuk Kepemimpinan Kristen Yang Efektif Masa Kini - Butar Butar, Rudy (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2024)
Leadership helps organizations, institutions, or institutions to achieve their goals optimally and effectively. Without the leadership function being implemented or applied consistently, an organization will not run as expected, including Christian leadership (churches or Christian service institutions). This research seeks to emphasize the importance of implementing leadership in Christian organizations and therefore this research aims to describe John C. Maxwell's thoughts on leadership for effective Christian leadership. The research method used is descriptive, namely describing thoughts that contribute to answering existing research problems. It was found that Maxwell's leadership model, especially the characteristics of effective leadership, has contributed to effective Christian leadership today.